Between the State and civil society: participatory institutions and the solidarity economy movement - Moura de Oliveira, Gustavo (Cooperativismo & Desarrollo, 2017)
Introduction: Since 2003, with the arrival of the Workers' Party (pt) to the Federal Government, there has been a notable and committed closeness of civil society to the State in Brazil. Institutions of social participation –or participatory institutions– already existing expanded and new ones arose. Aware of this, the solidarity economy movement sought to occupy these spaces.Purpose: This article aims to revisit the concepts of participatory institutions so that understanding about how they have operated in practice and their effectiveness on participation itself is made possible. Therefore, the study aims to identify the participatory institutions ascribed to the solidarity economy, so as to understand what is the role proposed by the State for these institutions, as well as to analyze and distinguish if the solidarity economy movement is accessing these spaces in an effective way.Conclusions: It is possible to conclude that there already exist several participatory institutions linked to the solidarity economy and that, in the municipality of Canoas (in the department of Rio Grande do Sul, Brazil), the Municipal Forum of Solidarity Economy has played a decisive role in the division of power between the State and civil society. Nonetheless, there is still much left to progress towards en effective participatory democracy in the municipality and in the country.
Keywords: solidarity economy; State; participatory institutions; social movements; civil society